Bibliometric Mapping of Religious Moderation Research in Islamic Education and Metaverse Technologies (2020–2025) - Putri, Lasmi Anisa; Kustati, Martin; Bashori, Bashori (Unisia, 2025)
This study examines research trends on religious moderation in Islamic education in relation to metaverse technology during the period 2020–2025, responding to the growing urgency of integrating wasathiyah values with emerging immersive digital environments. The primary objective is to map the intellectual structure, thematic evolution, and research gaps at the intersection of religious moderation, Islamic education, and metaverse-related technologies. Using a bibliometric approach, the study analyzed publications indexed in the Scopus database through keyword-based searches and processed the data with VOSviewer to generate co-authorship, co-citation, and keyword co-occurrence networks. The results reveal a steady increase in publications addressing religious moderation and Islamic education, while direct integration with metaverse concepts remains limited. Network and cluster analyses identify five major thematic clusters, including immersive learning technologies, religious moderation and tolerance, educational and socio-cultural contexts, supporting digital technologies and ethical challenges, and innovation and religious harmony. The findings indicate that although metaverse-related technologies such as virtual reality and augmented reality are increasingly discussed in educational research, their application to fostering religious moderation in Islamic education is still fragmented and underexplored. This gap highlights weak interdisciplinary collaboration between education scholars and technology researchers. In conclusion, the study demonstrates that religious moderation in Islamic education is an expanding field with significant potential for integration with metaverse-based learning environments. The findings provide a comprehensive knowledge map and offer strategic insights for future research, policy development, and pedagogical innovation aimed at promoting tolerant, inclusive, and human-centered Islamic education in digital and immersive contexts.